2021
DOI: 10.3389/fneur.2021.658527
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as a Predictor of Cognitive Decline in an Elderly Essential Tremor Cohort: A Prospective, Longitudinal Study

Abstract: Background: Essential tremor (ET), one of the most common neurological diseases, is associated with cognitive impairment. Surprisingly, predictors of cognitive decline in ET remain largely unidentified, as longitudinal studies are rare. In the general population, however, lower physical activity has been linked to cognitive decline.Objectives: To determine whether baseline physical activity level is a predictor of cognitive decline in ET.Methods: One hundred and twenty-seven ET cases (78.1 ± 9.5 years, range =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In general, studies conclude that factors such as smoking, depressive disorders, diabetes mellitus, metabolic syndrome and APOE ε4 genotype are associated with greater cognitive decline, whereas better physical health, physical activity, Mediterranean diet and cognitive training are protective factors. However, no studies have been found that indicate that it affects women more than men or vice versa [107,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131].…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…In general, studies conclude that factors such as smoking, depressive disorders, diabetes mellitus, metabolic syndrome and APOE ε4 genotype are associated with greater cognitive decline, whereas better physical health, physical activity, Mediterranean diet and cognitive training are protective factors. However, no studies have been found that indicate that it affects women more than men or vice versa [107,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131].…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Exercise in general is defined as a protective factor of neurological capacity and cognitive impairment. Studies have shown that an increased amount of exercise in the general population leads to improved cognition, highlighting the neuroprotective benefits of physical activity [23,24]. One of the most utilized types of exercise in programs for the management of hand tremors is resistance training [25], which may provide considerable benefit to participants with a hand tremor, especially those who experience greater tremor intensity in one limb compared to the other.…”
Section: Introductionmentioning
confidence: 99%